(untitled) (Proximus Journal of Sports Science and Physical Education, 2024)
The improvement of the educational system, its quality, and its efficiency is closely connected to a range of factors that become apparent during the teaching process. The measures undertaken in our country to prepare highly qualified specialists, along with the laws and decrees developed, embody these critical factors. The individual approach plays a significant role in fostering professional motivation in students within the educational process.